2015
DOI: 10.5460/jbhsi.v7.2.47718
|View full text |Cite
|
Sign up to set email alerts
|

Aprendizaje comprensivo: evaluación de la habilitación lingüística en modos complementarios

Abstract: Una de las condiciones identificadas en el marco del análisis experimental del aprendizaje comprensivo corresponde a la habilitación lingüística. Esta se ha definido como la facilitación de un desempeño en modo activo lingüístico o no lingüístico como resultado de la exposición a uno reactivo. Se realizó un experimento con el fin de evaluar la habilitación lingüística entre modos reactivos-activos complementarios en el aprendizaje de la propiedad conmutativa de la suma a partir de la exposición a cinco niveles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Similar studies have shown higher reading comprehension rates in learning situations in reading-writing (reading or reading-writing) linguistic modes, and that better results are obtained in the substitution and referential substitution levels, contrasted with the substitute non-referential level (Cárdenas & Guevara, 2013;Tamayo & Pulido, 2015;Velarde & Bazán, 2017).…”
Section: Discussionmentioning
confidence: 69%
“…Similar studies have shown higher reading comprehension rates in learning situations in reading-writing (reading or reading-writing) linguistic modes, and that better results are obtained in the substitution and referential substitution levels, contrasted with the substitute non-referential level (Cárdenas & Guevara, 2013;Tamayo & Pulido, 2015;Velarde & Bazán, 2017).…”
Section: Discussionmentioning
confidence: 69%